Geology And The Effect Of Boulder Size Concretion To Bauxite Laterite Deposit Quality At Djanra Area, Sandai District, Ketapang Regency, West Kalimantan - Sutarto, Sutarto; Harjanto, Agus; Kurniawan, Paschalis Pindyka Aji (Journal TECHNO, 2022)
The research area is located in Djanra areas Sandai District, Ketapang Regency, West Kalimantan. The research methods used are surface geological mapping, bauxite sample collection, also studio and laboratory analysis. Laboratory analysis includes petrographic analysis, XRF, and wet analysis. The geomorphology of the study area is dominated by denudational and anthropogenic landforms as a result of mining activities. The constituent rocks are Kerabai andesite units which are Middle-Late Cretaceous and are intruded by Sukadana trachyte units which are of Late Cretaceous period. The geological structures found are a shear joint with the main southwest-northeast direction and the normal right slip fault. Bauxite laterite deposits in the research area have varying overburden and ore thicknesses. Distribution of concretion size of boulder to depth in the study area varies. Based on the results of the study, the boulder size concretion can affect the quality of bauxite laterite deposits. Where on DJANRA-1 hill is declared feasible to be taken and mixed with smaller concretions because it meets quality standards.